Local-made Craft as Tourist Village Souvenirs: Challenges and Opportunities - Kurniawan, Taufiq; Ivan Suaidi; Ermawati; Riza Laely Ikayanti; Siti Nur Hidayati (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
Loyok is one of the villages in the Sikur sub-district, East Lombok Regency, West Nusa Tenggara which resides in the southern part of Mount Rinjani. This village constitutes one of the central woven bamboo handicrafts. These local crafts require development the so-called tourism village souvenir products. The development of local craft-based tourist village souvenirs is expected to be the start of increasing the value of local crafts in Loyok village. This article describes the opportunities and challenges as well as formulates a strategy for developing local craft-based tourist village souvenirs in Loyok village which is the center of bamboo handicrafts. The method used is in the form of a qualitative descriptive which begins with collecting data from interviews with informants, they are all business actors of woven bamboo craftsmen in Loyok village, filling out questionnaires by tourists visiting Loyok village, as well as documentation directly to the location of making woven bamboo handicrafts in Loyok village. Meanwhile, the technique of formulating a strategy for developing woven bamboo handicrafts into village tourism souvenirs based on local crafts is carried out through a SWOT analysis. The results and discussion will be discussed further.